Mobile license renewal : what are the issues? what is at stake ? - Guermazi, Boutheina (Policy research working paper, 2005)
"A major challenge facing regulators in industrial and developing countries alike is the need to strike the right balance between ensuring certainty for market players and preserving flexibility of the regulatory process to accommodate the rapidly changing market, technological, and policy conditions. This challenge applies across a wide range of regulatory instruments and vehicles including license renewal, which is the focus of this paper. The authors provide an overview of mobile license renewal issues covering the legal regime of license renewal, the renewal process, the non-renewal context, and the changes in licensing conditions, including spectrum implications of the renewal process. They draw best practices that started to emerge in recent renewal practices, to ensure that the renewal process leads to the best outcome for all stakeholders. As much as possible, policymakers and regulators should strive to promote investors' confidence and give incentives for long-term investment. They can do this by favoring the principle of "renewal expectancy," but also by promoting regulatory certainty and predictability through a fair, transparent, and participatory renewal process. For example, by providing details for license renewal or reissue, clearly establishing what is the discretion offered to the licensing body, or ensuring sufficient lead-times and transitional arrangements in the event of non-renewal or changes in licensing conditions. Public consultation procedures and guaranteeing the right to appeal regulatory decisions maximizes the prospects for a successful renewal process. As technological changes and convergence and technologically neutral approaches gain importance, regulators and policymakers need to be ready to adapt and evolve licensing procedures and practices to the new environment. "--World Bank web site